Influência da Salmonella Enterica Sorovar Typhimurium sobre a virulência da Entamoeba Dispar e da Entamoeba Histolytica in vitro e na colite amebiana experimental - Fabrício Marcus Silva Oliveira (2016)
Amebiasis is the most serious protozoa that hits the human intestine and is the second-leading cause of death among parasitic diseases, surpassed only by malaria. It is considered that only Entamoeba histolytica is able to penetrate tissues and produce invasive amebiasis. However, some studies have shown that Entamoeba dispar is capable of producing lesions in experimental models. In order to determine if the enteropathogenic bacteria contribute to increase the gene expression of amebic virulence factors, as well as to induce more intense lesions, we propose to evaluate the influence of Salmonella Enterica sorovar Typhimurium on the virulence of Entamoeba dispar and Entamoeba histolytica in trophozoites isolated from the in vitro culture and pathologically evaluate amoebic colitis in rats infected with amoebic trophozoites and co-infected with S. typhimurium. E. dispar, MCR, ADO and VEJ strains from E. dispar and, EGGp and EGGa from E. histolytica were cultured separately and associated or not with the S. Typhimurium bacterium. Then, the RNA extraction from these cultures was carried out to produce cDNA from the virulence factors of E. histolytica and E.dispar and quantified the expression of the virulence factors. For the induction of amoebic colitis, 8 wistar rats (Rattus norvegicus) per group, previously submitted to an intragastric intubation of S. Typhimurium, were inoculated by the intracecal route with 5x105 trophozoites. As control groups, 40 rats were only inoculated with amebian trophozoites from the Entamoeba strains studied. Another 16 rats were the control groups infected only with S. typhimurium and uninfected control. All rats were sacrificed 7 days after amebic infection to collect cecum, histological slides for histopathological and morphometric analysis, and for the immunohistochemical anti-IL1á, IL4, COX-2 and MUC-2 immunohistochemical reactions . Our study showed that the co-culture of E. dispar with the S. typhimurium enterobacterium was able to increase the expression of amebaporo A, cysteine proteinase-5 and Galactose-binding lectin and N-acetylgalactosamine virulence factors. Contrary to what was observed by other authors, E. dispar strains studied by us were able to express the amoebic virulence factor cysteine proteinase-5. The co-culture of E. histolytica with the S. typhimurium enterobacterium was able to increase the expression of the amebian virulence factor amebaporo A. We also found that in the majority of the groups analyzed, the in vivo association of E. dispar or E. histolytica with S. typhimurium was able to increase the intensity of ulcerative amebic colitis, also accompanied by increased expression of proinflammatory mediators and reduced IL-4 expression. In addition, in most of the analyzed groups, the in vivo association of E. dispar or E. histolytica with S. typhimurium was able to increase MUC-2 mucin expression, due to the greater intensity of aggression to the colonic mucosa. In view of the results obtained, we conclude that the interaction of S. Typhimurium with E. dispar and E. histolytica was able to increase the virulence of these species of amoebae leading to ulcerative amebic colitis of greater intensity.